Body dissatisfaction and low self-esteem in elementary school-aged children: the role of media pressure and trust in parent–child relationships - De Coen, Jolien; Verbeken, Sandra; Goossens, Lien (Frontiers in Psychology, 2024)
Studies have indicated that the media plays a role in the development of body dissatisfaction in children. Nevertheless, there is limited understanding of the protective factors that may reduce this association, such as the parent-child relationship. Therefore, this study investigates children's body dissatisfaction and self-esteem and the role of media pressure and a trust in parent-child relationships herein. A sample of n = 246 participants (59.8 % girls, aged 8-10) was recruited. Children completed self-report questionnaires that assessed body dissatisfaction, self-esteem, media pressure, and trust in parent-child relationships. Results revealed that higher scores on media pressure were linked to increased body dissatisfaction and decreased selfesteem. On the other hand, higher scores on trust in mother and father were associated with lower levels of body dissatisfaction and higher levels of self-esteem. However, the presence of trust in parent-child relationships did not attenuate the impact of media pressure on body BODY DISSATISFACTION, LOW SELF-ESTEEM, MEDIA PRESSURE AND A POSITIVE PARENT-CHILD RELATIONSHIP 2 dissatisfaction or self-esteem. Further investigation is necessary to gain a deeper understanding of how sociocultural and interpersonal factors interact and contribute to the development of body image problems. While current prevention and intervention programs predominantly focus on the individual, it may be beneficial to place greater emphasis on the family environment. Highlights -Media pressure is associated with more body dissatisfaction and less self-esteem -More trust in parent-child relationships is associated with less body dissatisfaction and more self-esteem -Both the relationship with the mother, as well as with the father play a role in children's body evaluation and self-esteem -Trust in parent-child relationships did not attenuate the association between media pressure and the outcomes Reference list